2008
DOI: 10.1109/tvcg.2008.127
|View full text |Cite
|
Sign up to set email alerts
|

EMDialog: Bringing Information Visualization into the Museum

Abstract: Abstract-Digital interactive information displays are becoming more common in public spaces such as museums, galleries, and libraries. However, the public nature of these locations requires special considerations concerning the design of information visualization in terms of visual representations and interaction techniques. We discuss the potential for, and challenges of, information visualization in the museum context based on our practical experience with EMDialog, an interactive information presentation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 11 publications
4
113
0
Order By: Relevance
“…We introduce these as characteristics of a design space that applies to research on literary collections specifically, but also to humanities research at large. This space differs from related application contexts that have previously been discussed in the visualization research community, such as casual or artistic scenarios [33], libraries [46], museums [3,21], or journalism [5] by drawing from and expanding recent digital humanities discussions that seek to address critically the potential of information visualization in their research [13,16,17,25,27]. We posit four dimensions that characterize this space-the audience, research approaches within the humanities (quantitative analysis vs. interpretation), the role of visualization (result vs. process), and considerations on material and visual aspects of the source material.…”
Section: Visualization In the Humanities: The Design Spacementioning
confidence: 99%
See 2 more Smart Citations
“…We introduce these as characteristics of a design space that applies to research on literary collections specifically, but also to humanities research at large. This space differs from related application contexts that have previously been discussed in the visualization research community, such as casual or artistic scenarios [33], libraries [46], museums [3,21], or journalism [5] by drawing from and expanding recent digital humanities discussions that seek to address critically the potential of information visualization in their research [13,16,17,25,27]. We posit four dimensions that characterize this space-the audience, research approaches within the humanities (quantitative analysis vs. interpretation), the role of visualization (result vs. process), and considerations on material and visual aspects of the source material.…”
Section: Visualization In the Humanities: The Design Spacementioning
confidence: 99%
“…This strategy has been extensively discussed in the visualization community to facilitate investigative analysis [45,53], the exploration of news articles [11], book collections [46], and artworks [21]. Studies have shown that the strategy of coordinated views is useful for the analysis of large and complex document collections, both in professional [5,18] and casual contexts [11,21]. Thudt et al highlight this strategy as particularly effective for supporting open-ended exploration and serendipitous discoveries [46].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, research has shown that playfulness can distract learners from their tasks (cf. Hinrichs et al, 2008or Sugimoto, 2009). …”
Section: Summary and Discussionmentioning
confidence: 99%
“…Furthermore, when applications are designed in a fun and playful manner, they can distract learners from the learning task (cf. Hinrichs et al, 2008or Sugimoto, 2009. To avoid such negative implications, a 'minimal design' was chosen.…”
Section: Design Of the Graphical User Interfacementioning
confidence: 99%